(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prayoga GI, Henri, Mustikarini ED, Anggyansyah. 2022. Diversity and morphological relationship of orchid species (Orchidaceae) in Bangka Island, Indonesia. Biodiversitas 23: 5323-5332. The population of orchid plants has suffered extinction due to the conversion of forest land functions. Efforts to preserve orchids can be carried out through exploration, identification and conservation activities. Diversity and morphological information are useful for resource management, conservation, hybridization, and genetic improvement of orchids. This research was to determine the diversity and relationship of orchids on Bangka Island based on morphological characters. This research was conducted in four districts in Bangka Island, namely Central Bangka, West Bangka, Bangka, and South Bangka. The research method used is a survey method with a convenience sampling technique. Observed data were analyzed descriptively and calculated for diversity index, evenness index, species richness index, and morphological relationship. Analysis of morphological relationship was done using UPGMA (Unweighted Pair Group Method with Arithmetic Mean). The results of the study found 17 species of orchids in Bangka Island i.e. Bulbophyllum subumbellatum, Podochilus microphyllus, Crepidium calophyllum, Phalaenopsis cornu-cervi, Cymbidium finlaysonianum, and Malaxix kobi. Bangka District found 10 species, namely Phalaenopsis sumatrana, Liparis rhombea, Bulbophyllum sp., Robiquieta spathulata, Liparis sp., Trichotosia velutina, Micropera collosa, Dendrobium aloifolium, Grammatophyllum speciosium, and Adenoncos major. Exploration in West Bangka District and South Bangka District only found the same orchid species, namely Acriopsis javanica. The orchid species on Bangka Island have moderate diversity, high evenness index, and low species richness index. The relationship of orchid species in Bangka Island based on morphological characters has 60% similarities which are divided into 9 clusters. Prevention of orchid population reduction on Bangka Island can be done by using in situ and ex-situ conservation methods. In addition, for the future development of orchids, crosses between orchids that have unique characters and distant morphological relationships can also be carried out to produce orchids for commercial purposes.